HUBUNGAN PENGETAHUAN ORANG TUA DENGAN KONDISI MALOKLUSI PADA ANAK YANG MEMILIKI KEBIASAAN BURUK ORAL - Ratna Citra Nabila; Risti Saptarini Primarti; Iwan Ahmad (Journal of Syiah Kuala Dentistry Society, 2017)
Parents dental knowledge and awareness are the basis of the formation for supporting or unsupportive habits for the childrens dental growth. Bad oral habit is a normal condition in the beginning of childrens life, but it should be informed that this may continue exceeding the normal stage of growth and result in abnormality in the dento facial structure, such as malocclusion. It is highly suggested that parents to be alert in preventing malocclusion caused by the continuing bad oral habit. This study, therefore, aims to identify the correlation between parents dental knowledge and the malocclusion condition on children with bad oral habit. Data are treated with correlation analysis with 100 samples of children at the age of 8 to 10 years old with bad oral habits who visit the dental clinic at Public Health Center District of Pancoran (Puskesmas Kecamatan Pancoran). Samples are drawn using the accidental purposive sampling technique from oral clinical observations and questionnaire handed to the parents. Statistic test used in this study is bivariat analysis with chi square test.The results show that the majority of the parents have an adequate knowledge (46%) on oral bad habits and malocclusion. Most of the children suffer from severe malocclusion (71%), while the rest are free from the condition. It can be concluded from the findings that there is no correlation between parents knowledge and awareness on their childrens bad oral habits and the malocclusion condition.Keywords: dental knowledge, malocclusion, bad oral habits